Complications associated with deep brain stimulation for Parkinson's disease: a MAUDE study. (3rd September 2021) - Ward, Max; Ahmed, Mohsen; Markosian, Christopher; Ezike, Judith Z.; Agrawal, Rishav; Randhawa, Karandeep; Liang, Zhijia; Abraham, Mickey; Paskhover, Boris; Mammis, Antonios
Abstract: Introduction: Deep brain stimulation (DBS) is a common surgical option for the treatment of medically refractory Parkinson's disease (PD). Manufacturer and User Facility Device Experience (MAUDE), a United States Food and Drug Administration (FDA)-compiled database of adverse event reports related to medical devices, is a public resource that can provide insight into the relative frequency of complications and patient complaints. Materials and Methods: We accessed the MAUDE database and queried for adverse reports for deep brain stimulators implanted for PD from January 1, 2009 to December 31, 2018. Complaints were classified into device malfunction, patient non-compliance, patient complaint, surgically managed complications (i.e. complications that are corrected via surgery), and death. Patient complaints were further stratified into ineffective stimulation, shock, overstimulation, battery-related problems, or pain at the pulse generator site. Surgically managed complications were classified as intraoperative complications, impedance, migration, erosion, infection, lead fracture, and lead disconnection. Each event could receive multiple classifications and subclassifications. Results: A total of 4, 189 adverse event reports was obtained. These encompassed 2, 805 patient complaints. Within this group, 797 (28%) events were classified as ineffective stimulation. There were 1, 382 surgically managed complications, 104 (8%) of which were intraoperative complications, 757 (55%) documented impedance issues, 381 (28%) infections, and 413 (30%) lead-related issues. There were 53 documented deaths. Conclusions: The MAUDE database has potential use as a real time monitor for elucidating the relative occurrence of complications associated with deep brain stimulation. It also allows for the analysis of device-related complications in specific patient populations. Although the database is useful in this endeavor, it requires improvements particularly in the standardization of reporting adverse events.